(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize core physiological mechanisms underlying nociceptive reflexes and the body’s natural pain-inhibitory systems, and to appraise non‑pharmacologic strategies that harness endogenous analgesia. Method: We narratively reviewed landmark primary studies and authoritative reviews on pain physiology and modulation covering gate control, spinal-brainstem descending systems, diffuse noxious inhibitory controls/conditioned pain modulation, placebo/opioid‑dependent mechanisms, mindfulness‑related analgesia, exercise‑induced hypoalgesia, and transcutaneous electrical nerve stimulation. Selection prioritized highly cited, peer‑reviewed works with mechanistic clarity and human relevance. Results: Pain reflexes arise from activation of peripheral nociceptors with segmental spinal integration and rapid protective motor outputs; perception is shaped by ascending-descending interactions. Endogenous inhibition involves segmental gating in the dorsal horn, and supraspinal control via periaqueductal gray-rostral ventromedial medulla and locus coeruleus that project to the dorsal horn through opioidergic, serotonergic, and noradrenergic pathways. DNIC/conditioned pain modulation indexes the integrity of these systems. Psychobiological factors including expectation (placebo), attention/mindfulness, and acute exercise recruit overlapping modulatory circuits. Noninvasive somatosensory input (e.g., TENS) engages large‑fiber gating and descending inhibition. Conclusion: Natural analgesic inhibition is multi‑layered segmental, brainstem, and cortical and can be amplified with behavioral and sensory interventions. Understanding these mechanisms supports rational, low‑risk, multimodal approaches to pain management and provides physiological endpoints (e.g., conditioned pain modulation) for phenotyping and treatment tailoring.